Towards an extended festival viewing experience - Velt, Raphael; Benford, Steve; Reeves, Stuart; Evans, Michael; Glancy, Maxine; Stenton, Phil (2015)
Media coverage of large-scale live events is becoming increasingly complex, with technologies enabling the delivery of a broader range of content as well as complex viewing patterns across devices and services. This paper presents a study aimed at understanding the experience of people who have followed the broadcast coverage of a music festival. Our findings show that the experience takes a diversity of forms and bears a complex relationship with the actual experience of being at the festival. We conclude this analysis by proposing that novel services for coverage of this type of events should connect and interleave the diverse threads of experiences around large-scale live events and consider involving more diverse elements of the experience of “being there”.